-3(2m-4)=-4m+18

Apply the distributive property.

-3(2m)-3⋅-4=-4m+18

Multiply.

Multiply 2 by -3.

-6m-3⋅-4=-4m+18

Multiply -3 by -4.

-6m+12=-4m+18

-6m+12=-4m+18

-6m+12=-4m+18

Add 4m to both sides of the equation.

-6m+12+4m=18

Add -6m and 4m.

-2m+12=18

-2m+12=18

Subtract 12 from both sides of the equation.

-2m=18-12

Subtract 12 from 18.

-2m=6

-2m=6

Divide each term in -2m=6 by -2.

-2m-2=6-2

Cancel the common factor of -2.

Cancel the common factor.

-2m-2=6-2

Divide m by 1.

m=6-2

m=6-2

Divide 6 by -2.

m=-3

m=-3

Solve for m -3(2m-4)=-4m+18